Analisis Kepuasan Kerja Pegawai Pada Inspektorat Kabupaten Mandailing Natal - Nora, Agustalinda; Batubara, Hery Dia Anata; Sari, Diana; Maharani, Fithra; Pane, Pertama Yul Asmara; Batubara, Rizky Husada (Yayasan Jompa Research and Development, 2024)
The purpose of this study was to determine the level of employee job satisfaction at the Mandailing Natal Regency Inspectorate Office. The method used in this research is descriptive method with quantitative approach and verification method. The types and sources of data for this research are primary and secondary data. The data collection techniques used are interviews, observations and questionnaires. From the results of the discussion, it is concluded that the category of job satisfaction level of Mandailing Natal Regency Inspectorate employees is